The performance of some meta-heuristics in continuous problems studied according to the location of the optima in the search space (2013)
Many hard optimization problems can only be effectively handled by meta-heuristic methods. Some continuous optimization problems have specifi c characteristics that demand a particular interest. These features include the location of the optima in a specifi c region of search space. Hence the main goal of this paper is assessing the  performance of some outstanding population-based meta-heuristics on functions with optima on bounds and problems with optima off bounds. It is studied by taking a set of benchmark functions from the fi eld of optimization as a point of departure.